2016
DOI: 10.1097/md.0000000000005490
|View full text |Cite
|
Sign up to set email alerts
|

Does the interval of screening endoscopy affect survival in gastric cancer patients?

Abstract: Gastric cancer remains the second most common cancer in Korea; however, its mortality has decreased due to earlier diagnosis. In Korea, screening endoscopy has been performed nationwide since 1999. The aim of this study was to elucidate the benefit of screening endoscopy on actual survival in gastric cancer patients and to determine the optimal interval of screening endoscopy.We analyzed 1651 patients diagnosed with gastric adenocarcinoma who underwent surgical treatment between June 2008 and December 2014. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…As a result, the 5-year GC-specific survival rates of < 2 years interval group were significantly higher than > 2 years interval group and the risk of AGC decreased in < 2 years interval group. 24 In addition, a 1-year GC screening interval is beneficial for patients with severe intestinal metaplasia in another study. 5 As mentioned above, our study showed that both endoscopic intervals of < 2 years and 3 years are appropriate for EGC detection.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As a result, the 5-year GC-specific survival rates of < 2 years interval group were significantly higher than > 2 years interval group and the risk of AGC decreased in < 2 years interval group. 24 In addition, a 1-year GC screening interval is beneficial for patients with severe intestinal metaplasia in another study. 5 As mentioned above, our study showed that both endoscopic intervals of < 2 years and 3 years are appropriate for EGC detection.…”
Section: Discussionmentioning
confidence: 96%
“… 22 23 Other studies have suggested that biennial endoscopic screening can increase the rate of early detection of EGC and reduce the number of cases of progression to AGC. 10 24 In one cross-sectional study of these reports, the authors analyzed GC patients except the group of endoscopic resection as a treatment of GC. As a result, the 5-year GC-specific survival rates of < 2 years interval group were significantly higher than > 2 years interval group and the risk of AGC decreased in < 2 years interval group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted in Korea have concluded that the interval of endoscopic screening could be expanded to 2–3 years based on the stage distributions of the detected cancers and the previous endoscopic examinations [ 19 21 ]. In a nested case-control study conducted under a Korean national program, reduction in gastric cancer mortality could be confirmed even if the patients were screened only once within 4 years or more after the diagnosis of gastric cancer for case groups [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients were excluded if they satisfied any of the following exclusion criteria: remnant stomach, familial adenomatous polyposis (FAP), or lack of data years before detection (including cases without identified lesion location in the initial EGD). Included cases were classified as a slow-growth group, comprising patients whose findings showed cancer in previous endoscopic images ( Figure 1 ), or a rapid-growth group, comprising cases whose findings showed no cancer in previous endoscopic images ( Figure 1 ) [ 6 , 13 , 14 ]. The study protocol was approved by the ethics committee/institutional review board at Hyogo College of Medicine, Japan (approval no.…”
Section: Methodsmentioning
confidence: 99%